2022
DOI: 10.33546/bnj.2018
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of surgical site infection prevention among operating room nurses in southwest China

Wen Feng,
Wipa Sae-Sia,
Luppana Kitrungrote

Abstract: Background: Surgical site infection has become a problem in the operating room, and the nurses’ knowledge, attitude, and practice could impact the incidence of the infection. Unfortunately, there is a dearth of studies on this issue in China. Therefore, determining nurses’ knowledge, attitude, and practice of surgical site infection prevention is necessary. Objectives: This study aimed to examine the knowledge, attitude, and practice of surgical site infection prevention and their relationships, as well as to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The findings of the present study are consistent with a study conducted by Jaleta (6), who found that out of 256 participants (67.4 %) of the study sample is in the age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of the present study are consistent with a study conducted by Jaleta (6), who found that out of 256 participants (67.4 %) of the study sample is in the age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years.…”
Section: Discussionsupporting
confidence: 93%
“…This study revealed that nearly 60% of participants had no previous infection control training, (20). A study was disagree with this study finding , showed that 66.7% of participants had participated in the training program fewer than five times over the previous two years, (21).…”
Section: Discussionmentioning
confidence: 54%
“…[26] The study's findings contrast with a previous study in China, which revealed that 43.5% of participants exhibited a low level of knowledge. [19] This study involved healthcare professionals including nurses, midwives, physicians, anaesthetists, and anaesthesiologists from the surgical team, who significantly contribute to preventing SSIs in surgical patients during preoperative, intraoperative, and postoperative periods.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Another study conducted in China indicated that nurses knowledge of surgical site infection prevention was at a low level. [19] A study in Ireland found that healthcare professionals' lack of knowledge about SSIs prevention guidelines is a significant contributor to SSIs. [20] Studies in Ethiopia and Cameroon reveal insufficient knowledge and practice among nurses in preventing SSIs due to factors like limited experience, education, workload, infection prevention training, and patient safety guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation